From the History of Armenian Phonetic Stylistics - Berberyan, Valter (Bulletin of Yerevan University B: Philology, 2023)
Different linguists studied the phonetic system of Armenian, performing many laboratory tests. Armenian is a harmonious language by the nature of the phonetic system. It has high musicality data as well. The phonology of the modern Armenian language describes and classifies the phonetic system of the modern stage of the Armenian language, reveals the phonetic processes taking place in the language, the changes in the different order of sounds, the reasons for their occurrence, the patterns. The article presents the problems of phonetic stylistics development. We have studied the works written about phonetic stylistics of the Armenian language, the provisions in various researches. Reference was made to the main components of phonetic stylistics: alliteration, assonance, onomatopoeic word. The methodological basis is the combination and analysis of existing theoretical provisions.